If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 2x + 4y = 0 Solving 12 + 2x + 4y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + 2x + -12 + 4y = 0 + -12 Reorder the terms: 12 + -12 + 2x + 4y = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 2x + 4y = 0 + -12 2x + 4y = 0 + -12 Combine like terms: 0 + -12 = -12 2x + 4y = -12 Add '-4y' to each side of the equation. 2x + 4y + -4y = -12 + -4y Combine like terms: 4y + -4y = 0 2x + 0 = -12 + -4y 2x = -12 + -4y Divide each side by '2'. x = -6 + -2y Simplifying x = -6 + -2y
| 200=100(1.04)x | | h-9.2=28 | | 34x+4=106 | | F(200)=100(1.04)x | | -134-10x=58+2x | | -87=9+x | | 6x^2+12x^2-7x= | | F(200)=100(1.04)200 | | X+7=1+7x | | -54=-42+n | | x+13y+8y= | | x+3-2x=75 | | 9*n=2.5 | | 2a+4a=1 | | Z+4(z+3)=15 | | 9=8y | | -46+12x=38+5x | | 20x-60=10x-10 | | 7x-a=6a | | 7+6x=-5x+95 | | 2(c+6)=5(5+12) | | 10x^2-30=5x^2+5 | | 6(x^2-10x+25)=1 | | 7-4x=-7x+10 | | 3x+24+7x-8=180 | | (x+12)+6+12+3(x+6)=58.5 | | 6x-36=3(x-5) | | 3x+24+7x-8=18 | | 65x+30=2505 | | 5X+3=5(2-3X) | | 5(x-5)-3= | | 8p+2q=36 |